1999
DOI: 10.1046/j.1523-1747.1999.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal Dermal–Epidermal Separation and Fibronectin Cleavage in Basement Membrane by Human Mast Cell Tryptase

Abstract: Mast cell proteases are believed to participate in the basement membrane destruction in blistering diseases. Thus, normal human skin specimens were incubated with purified human skin tryptase or compound 48/80 (a mast cell degranulator) for up to 24 h. Thereafter, the specimens were studied immunohistochemically. Tryptase caused, in the presence and absence of 1,10-phenanthroline, focal dermal-epidermal separation above laminin and almost complete disappearance of the staining of the extra domain A region of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 41 publications
0
56
0
2
Order By: Relevance
“…Tryptase-positive mast cells are increased in number close to the psoriatic epidermis and, therefore, the enzyme may well aVect the basement membrane and basal keratinocytes. Indeed, tryptase has been found to degrade Wbronectin in the basement membrane zone [87]. In addition, tryptase can activate metalloproteinases, such as MMP-3 and MMP-9 [55, 75,102], and pro-urokinase [174], or it can act as a gelatinase [39].…”
Section: Mast Cell Serine Proteinases In Psoriasismentioning
confidence: 99%
“…Tryptase-positive mast cells are increased in number close to the psoriatic epidermis and, therefore, the enzyme may well aVect the basement membrane and basal keratinocytes. Indeed, tryptase has been found to degrade Wbronectin in the basement membrane zone [87]. In addition, tryptase can activate metalloproteinases, such as MMP-3 and MMP-9 [55, 75,102], and pro-urokinase [174], or it can act as a gelatinase [39].…”
Section: Mast Cell Serine Proteinases In Psoriasismentioning
confidence: 99%
“…For example histamine increases vascular permeability and rapid expression of P-selectin on the endothelium, leading to increased leakage of plasma and leukocyte rolling, adhesion and extravasation [5,6]. Furthermore, neutral proteases released following activation cleave basement membrane constituents including collagen [7] and fibronectin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that tryptase could also activate pro MMP-9 [23]. In addition, tryptase has previously been reported to cleave fibronectine in the pericellular matrix of fibroblasts, resulting in separation of the dermal-epidermal junction [20,24]. Although the mast cells are not in direct contact with the basement membrane (BM), the tryptase released as a result of AD could reach this zone, resulting in direct cleavage of the BM components, or indirect cleavage by the activation of MMPs.…”
Section: Discussionmentioning
confidence: 98%
“…Mast cell granules contain several mediators (TNF-α, PGE 2 and serine proteases) that could directly or indirectly modulate the degradation of the extracellular matrix or activate the proenzyme form of MMPs [19,20]. Previous studies have suggested that mast cell tryptase can activate MMP-1 through the activation of pro MMP-3 [21,22].…”
Section: Discussionmentioning
confidence: 99%